Prevalence of anaemia among females in reproductive age group attending a health center in the urban area of Kancheepuram district: a cross sectional study - Thoufiq, A. Abdul Azeez; Johnpaul, A.; Umadevi, R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Anaemia, which is defined as a low oxygen carrying capacity of blood, is a major public health problem. It is a condition in which there is a decrease in the total number of red blood cells in the blood, either due to decreased production or increased destruction or both. Anaemia, one of the most prevailing nutritional disorders, has a worldwide prevalence of approximately 52%. The burden of anaemia is high especially among females of reproductive age group where India ranks the top. The study is aimed to establish the prevalence of anaemia among female patients of reproductive age group (15-49 years). Methods: A cross sectional study was conducted among 254 females of reproductive age group, attending Anakaputhur, an urban field practice area of Sree Balaji Medical College. Convenient sampling method was used. Data was collected by discussion using a pretested semi-structured questionnare and haemoglobin estimation was done by venous sampling method. Results: The mean age of the study participants were 34.6±12.4 years with 9.05% uneducated and 8.6% graduate females. 26% gave history of symptoms of anaemia and prevalence of anaemia was reported to be 42.12% with 24.4%, 12.2% and 5.5% of mild, moderate and severe anaemia, respectively. Conclusions: Prevention and its treatment in women is much essential at this point, hence programmes and policies should be implemented based on the needs of the community, and health education should be imparted with respect to measures that can prevent and help in early diagnosis of anaemia.